2023
DOI: 10.3390/ani13152520
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Germ Cells Phenotype during Embryonic and Adult Development

Abstract: Primordial germ cells (PGCs) are the precursors of gametes. Due to their importance for the formation and reproduction of an organism, understanding the mechanisms and pathways of PGCs and the differences between males and females is essential. However, there is little research in domestic animals, e.g., swine, regarding the epigenetic and pluripotency profiles of PGCs during development. This study analyzed the expression of epigenetic and various pluripotent and germline markers associated with the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…More recently, in 2023 [ 75 ], Soares et al analyzed the expression of epigenetic, pluripotent, and germline markers associated with the development and differentiation of pPGCs at different gestational periods (from 24 to 35 days post-fertilization (dpf) and in adults) and with gender. They showed that the formation of the genital ridge from mesonephros at 24 days of gestation continues to develop until 29 days, when differentiation into primitive gonads begins, ending sexual dimorphism at 35 days of gestation.…”
Section: Production Of Competent Gametes In Livestockmentioning
confidence: 99%
“…More recently, in 2023 [ 75 ], Soares et al analyzed the expression of epigenetic, pluripotent, and germline markers associated with the development and differentiation of pPGCs at different gestational periods (from 24 to 35 days post-fertilization (dpf) and in adults) and with gender. They showed that the formation of the genital ridge from mesonephros at 24 days of gestation continues to develop until 29 days, when differentiation into primitive gonads begins, ending sexual dimorphism at 35 days of gestation.…”
Section: Production Of Competent Gametes In Livestockmentioning
confidence: 99%